Recueillir les toponymes inuit. Pour quoi faire ? - Collignon, Béatrice (HAL CCSD, 2005)
International audience Inuit toponymy has been quite popular among both Inuit and researchers (anthropologists and geographers alike), since the late 1980s. This short paper focuses on the issues at stake in projects dedicated to the collection of Inuit toponymies. Special attention is given to the process leading to their official recognition, by territorial and provincial governments, and by the Federal government. Through this process the Inuit' mental maps of their territories, that include hundreds of named places, become artefacts : paper maps published by the Department natural resources, and computer data bases. The process also implies that most English (or French) place names are replaced by Inuit ones. Building on her own experience of collecting place names among the Inuinnait (western central arctic, Nunavut and NWT), the author organises her discussion in three steps. First, a story is told : that of the difficulties met in having the 1007 Inuinnait place names collected in 1991-1992 processed in order to be recognised as official. Then, four highlights of a meeting held in Holman on August 12, 2003 are analysed. The meeting's goal was to review a set of blue-print maps sent by the Territorial Toponymy Program of the NWT. The maps showed all the Inuinnait place names that had been collected within today's NWT. This leads to the third step which questions the bureaucratic process of official recognition, the methods and scales adopted when conducting place name projects, and the problems related to transcribing a knowledge that is only kept alive as long as it is directly shared, through acts or words. Constatant l'engouement actuel pour les toponymies inuit, tant de la part des Inuit que des anthropologues et géographes, cette note de recherche propose une réflexion sur les enjeux des opérations de recueil des séries toponymiques inuit, qui se sont multipliées depuis la fin des années 1980. On considère notamment les processus de reconnaissance officielle par les gouvernements territoriaux ou ...